Tailored Limonene-Based Nanosized Microemulsion: Formulation, Physicochemical Characterization and In Vivo Skin Irritation Assessment - Mohammed M Mehanna; Kawthar Khalil Abla; Hoda A. Elmaradny (Tabriz University of Medical Sciences, 2021)
Purpose: Microemulsion (ME) achieved progressing consequences on both the research and industry levels due to their distinctive properties. ME based-limonene system is considered as a surrogate to the traditional microemulsion composed of conventional oils. Thus, a novel microemulsion based on D-limonene and Gelucire®44/12 had been designed and evaluated with assessing the factors affecting its physicochemical characteristics and in vivo skin irritation. Methods: The impact of microemulsion components and ratios on the isotropic region of the pseudo-ternary phase diagram was investigated. The optimal formula was evaluated in terms of percentage transmittance, average globule size, size distribution, zeta potential, microscopical morphology, stability under different storage conditions and its effect on the mice ear skin. Results: The results demonstrated that Labrasol® and Labrafil® M 1944 CS had been selected as surfactant and co-surfactant, respectively, due to their emulsifying abilities. The largest isotropic area in the pseudo-ternary phase diagram was at a weight ratio of 4:1 for Labrasol® and Labrafil® M 1944 CS. The optimized microemulsion with 25% w/w of the lipid phase and 58.3% w/w of the aqueous phase displayed an optical transparency of 96.5±0.88 %, average globule size of 125±0.123 nm, polydispersity index of 0.272±0.009, zeta potential of -18.9± 2.79 mV with rounded globules morphology and high stability. The in vivo skin irritation and the histopathological evaluation of microemulsion elucidated its safety profile when applied on the skin. Conclusion: The formulated microemulsion is a prospective aid for an essential oil to minimize its volatility, enhance its stability, and mask its dermal irritant.